Kurdish EFL teachers’ perspectives on assessment at university level: Factors, challenges, and washback - Ivan Murad; Sanan Shero Malo (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Assessment constitutes a fundamental component of educational process, shaping teachers’ instructional practices. However, its efficacy largely depends on the way teachers perceive assessment. Thus, this research article investigates Kurdish university-level English as a Foreign Language (EFL) teachers’ perspective on assessment in terms of the factors that influence their choice of assessment methods, their challenges in assessment, and the washback effects of assessment on students’ learning and study habits. Employing a quantitative approach, the study utilized a Likert-scale survey to collect data from a random sample of 75 teachers from 11 public universities in the Kurdistan Region of Iraq. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 25. The findings revealed several factors influencing teachers’ assessment choices, including strict institutional regulations, large class sizes, and students’ growing reliance on AI tools. The study also found that teachers face numerous challenges, such as detecting AI-generated work, limited access to technological resources, and balancing formative and summative assessments. Moreover, the results indicate that assessment practices generate both positive and negative washback, influencing students’ motivation, effort, and learning approaches. The study highlights the importance of aligning assessment practices with Kurdish EFL higher education principles to promote effective learning outcomes.